Comparative analysis of 3D CT values for different lumbar pedicle screw trajectories - Yuanpeng Yue; Ce Dong; Anhang Zhang; Zhenyu Wang (Journal of Orthopaedic Surgery and Research)
Abstract Study objectives The average CT values of the three-dimensional (3D) trajectories of transarticular surface (TAS) screws, traditional trajectory (TT) pedicle screws, and cortical bone trajectory (CBT) screws in the L4 and L5 vertebral bodies were evaluated, providing a radiological theoretical basis for the utilization of the transarticular surface screw trajectory (TAST) at these vertebral levels. Methods A retrospective analysis was conducted on 3D CT images of the lumbar spine from 300 patients aged 21–70 years obtained from January to August 2024. Using Mimics 21.0 software, cylindrical models were constructed to simulate three types of pedicle screws, and the average CT values of the target cylindrical area (TCA) were measured. Further exploration of the relationships between factors such as age, sex, lumbar segment, and average CT values for the TCA was conducted. Results Among the different age groups, the average CT value of the CBT group was the highest, followed by those of the TAS and TT screw groups (P < 0.05). Among patients of the same gender and age group, no significant difference was found in the average CT values of the same trajectory between the L4 and L5 vertebrae. Furthermore, in the 31–40 and 41–50 age groups, no significant difference was noted in the average CT values for the CBT between males and females. However, in the 21–30, 51–60, and 61–70 age groups, the average CT values of TT, CBT, and TAST were greater in males than in females (p < 0.05). Conclusions The average CT values of the L4 and L5 vertebral bodies for the TAST exceed those for the TT but are lower than those for the CBT. This radiological study offers a theoretical basis for using TAS screws in the L4 and L5 vertebral bodies.